Exploring the association between a cholecystokinin promoter polymorphism (rs1799923) and posttraumatic stress disorder in combat veterans. (December 2015) - Badour, Christal L.; Hirsch, R. Louis; Zhang, Jingmei; Mandel, Howard; Hamner, Mark; Wang, Zhewu
Highlights: Cholecystokinin (CCK) is a neuropeptide implicated in fear and anxiety. The study examined links between the CCK rs1799923 polymorphism in PTSD. Presence of a T allele was associated with increased PTSD prevalence. Abstract: Background: Cholecystokinin (CCK) is a neuropeptide that has been implicated in understanding the acquisition and extinction of fear. Research on CCK in anxiety has primarily focused on understanding panic attacks and panic disorder. Emerging data suggests that CCK may also hold promise in understanding the development and maintenance of posttraumatic stress disorder (PTSD). Method: The present study examined whether a single nucleotide polymorphism in the promoter region of the CCK gene (C > T; rs1799923) was associated with an increased prevalence of PTSD as well as with severity of PTSD symptoms among a sample of 457 combat veterans. Results: Results demonstrated that participants with either the heterozygous or homozygous T allele had an increased prevalence of PTSD relative to participants with the CC genotype (OR = 2.17; 95% CI [1.37–3.43]). Limitations: The relatively small sample size precluded examination of racial/ethnic differences. Findings were also limited by the absence of a systematic assessment of comorbid anxiety psychopathology. Conclusions: These data offer preliminary evidence supporting an association between the rs1799923 polymorphism in the CCK gene and PTSD. Additional research is needed to better understand the nature of this relationship.